Impediments of halal certification and logo in Malaysia / Ahmad Adl Azri Abdul Aziz, Nursuraya Mohamad Zulkifli and Syaza Fatini Shukri - Abdul Aziz, Ahmad Adl Azri; Mohamad Zulkifli, Nursuraya; Shukri, Syaza Fatini (2016)
Nowadays, Halalness became one of the most debatable topic for consumers especially to Muslim which is from the view point of Islamic practices and belief. In Malaysia, the submission of halal official recognition and logo depend on the request by food producers and entrepreneurs, and the holders of halal certificate gain the benefits of grapping a larger market because majority of Malaysian are Muslims (Ardyanti, et al., 2013). However, the advantages of halal certification are facing challenges that must be discussed.